2018
DOI: 10.32441/ijms.v1i3.99
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Diabetes and Pregnant Women with Urinary Tract Infections Compared to Younger Aged Female.

Abstract: Background: Urinary tract infection is common with health impact in women and characterised by failure to treatment and recurrent episodes. Aim: This study was conducted to determine the risk factors for the development of urinary tract infection in diabetic and pregnant women in comparison to student female. Materials and methods: A prospective cross-sectional study conducted during the period from 1st of June 2015 to the end of January 2016. The population included in the study are 563 women, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…was 2.The researcher's point of view is, whenever the number of family members inside the tent increase, the crowded increase also the stress increase and nutrition decrease due to poverty all those situations can lead to vaginal infection.Our study shows the effect of the accomodation duration on vaginal infection, this study found that Chi-Square 67.593, Sig .000 and DF was 1, the higher percentage of infected women 84.1% were in women who live in camp since years, while 15.9% found in women live in camp since months.the researcher's point of view is, many women in the camp reported that their vaginal infections increased when they entered the camp, the poverty of health care services, economic status beside insufficient environment of camp.The current study explained the higher ratio presented in infected women who the BMI (25.0-29.9 Overweight) was 35.9%, then (18.5-24.9 Normal) 31.7 %, (30.0-34.9 Obese (Class I)) 18.6%, (35.0-39.9 (Class II))11.0%, (40.0 and more(Class III)) 2.8%, Chi-Square55.724, Sig 0.000 and Df 4.The researcher's point of view is the fungal infection is exacerbating in overweight.The results of a study are in disagreement with a study of (Ventolini et al, 2017) (21) that found higher BMI. was associated with recurrent vulvovaginal bacterial infections in women of reproductive age, also approximately agreement with study of (Mahmoudi Rad et al, 2011) (22) who found 25% of infected women were overweight.Our study shows the infected women who get pregnant for (4-6) times was 40.7 the higher risk among infected women, and in the next rank comes the women who get pregnant for 7 times and more 30.3%, while the women who get pregnant for 1-3 times was 24.1%, the lesser ratio 4.8% was for the women who have ever become pregnant, Chi-Square81.724, Sig 0.000, Df 4The researcher point of view is multigravida women is more likely to be infected than nulligravida due to hormonal effects.These results are approximately agreement with (Essa & Hussein, 2018) (23) who found (%56.6) of infected women get pregnancy for 3-5 times.This study illustrates the infected women who have parity between (4-6) is having a higher ratio of 39.3%, then 31.0% for women who have parity between (1-3), parity 7and more is 22.8%, and finally the infected women who have no children get the percent 6.9%, Chi-Square33.290, Sig 0.000, DF3.The researcher point of view is the multipara women more likely to get vaginal infection because of hormonal fluctuation due to breast feeding or due to acquired infection during labor normally or cesarian. These results are disagreement with (Rathod & S., 2016) (23) who found (72.5%) women with vaginitis were nulliparous, (20%) were primipara, (5%) were second para and the remaining (2.5%) were para three and above.The study noted that most infected women 59.3% didn`t have any abortion status, lesser percent 3.4% found in women who have abortion between 4-6 times, chi-Square68.8693.503, Sig 0.000, Df 2.The researcher point of view is the women who exposing to curettage is more likely to acquired vaginal infection.These results are disagreement with (Essa & Hussein, 2018) (23) who found that 13.7% of infected women are having Abortion multiple times.This study reveals that majority of women with vaginal infection were higher percentage in non-pregnant women in 91.0% of them, and the rest percentage 5.5% and 3.4% among pregnant and those who have suspicious pregnancy, Chi-Square 217.338, Sig 0.000, Df 2.The researcher point of view is in pregnancy status estrogen hormone increase and lead to increase occurrence vaginal candidiasis.These results are disagreement with (Saeed et al, 2016)…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…was 2.The researcher's point of view is, whenever the number of family members inside the tent increase, the crowded increase also the stress increase and nutrition decrease due to poverty all those situations can lead to vaginal infection.Our study shows the effect of the accomodation duration on vaginal infection, this study found that Chi-Square 67.593, Sig .000 and DF was 1, the higher percentage of infected women 84.1% were in women who live in camp since years, while 15.9% found in women live in camp since months.the researcher's point of view is, many women in the camp reported that their vaginal infections increased when they entered the camp, the poverty of health care services, economic status beside insufficient environment of camp.The current study explained the higher ratio presented in infected women who the BMI (25.0-29.9 Overweight) was 35.9%, then (18.5-24.9 Normal) 31.7 %, (30.0-34.9 Obese (Class I)) 18.6%, (35.0-39.9 (Class II))11.0%, (40.0 and more(Class III)) 2.8%, Chi-Square55.724, Sig 0.000 and Df 4.The researcher's point of view is the fungal infection is exacerbating in overweight.The results of a study are in disagreement with a study of (Ventolini et al, 2017) (21) that found higher BMI. was associated with recurrent vulvovaginal bacterial infections in women of reproductive age, also approximately agreement with study of (Mahmoudi Rad et al, 2011) (22) who found 25% of infected women were overweight.Our study shows the infected women who get pregnant for (4-6) times was 40.7 the higher risk among infected women, and in the next rank comes the women who get pregnant for 7 times and more 30.3%, while the women who get pregnant for 1-3 times was 24.1%, the lesser ratio 4.8% was for the women who have ever become pregnant, Chi-Square81.724, Sig 0.000, Df 4The researcher point of view is multigravida women is more likely to be infected than nulligravida due to hormonal effects.These results are approximately agreement with (Essa & Hussein, 2018) (23) who found (%56.6) of infected women get pregnancy for 3-5 times.This study illustrates the infected women who have parity between (4-6) is having a higher ratio of 39.3%, then 31.0% for women who have parity between (1-3), parity 7and more is 22.8%, and finally the infected women who have no children get the percent 6.9%, Chi-Square33.290, Sig 0.000, DF3.The researcher point of view is the multipara women more likely to get vaginal infection because of hormonal fluctuation due to breast feeding or due to acquired infection during labor normally or cesarian. These results are disagreement with (Rathod & S., 2016) (23) who found (72.5%) women with vaginitis were nulliparous, (20%) were primipara, (5%) were second para and the remaining (2.5%) were para three and above.The study noted that most infected women 59.3% didn`t have any abortion status, lesser percent 3.4% found in women who have abortion between 4-6 times, chi-Square68.8693.503, Sig 0.000, Df 2.The researcher point of view is the women who exposing to curettage is more likely to acquired vaginal infection.These results are disagreement with (Essa & Hussein, 2018) (23) who found that 13.7% of infected women are having Abortion multiple times.This study reveals that majority of women with vaginal infection were higher percentage in non-pregnant women in 91.0% of them, and the rest percentage 5.5% and 3.4% among pregnant and those who have suspicious pregnancy, Chi-Square 217.338, Sig 0.000, Df 2.The researcher point of view is in pregnancy status estrogen hormone increase and lead to increase occurrence vaginal candidiasis.These results are disagreement with (Saeed et al, 2016)…”
Section: Resultssupporting
confidence: 92%
“…was associated with recurrent vulvovaginal bacterial infections in women of reproductive age, also approximately agreement with study of (Mahmoudi Rad et al, 2011) (22) who found 25% of infected women were overweight.Our study shows the infected women who get pregnant for (4-6) times was 40.7 the higher risk among infected women, and in the next rank comes the women who get pregnant for 7 times and more 30.3%, while the women who get pregnant for 1-3 times was 24.1%, the lesser ratio 4.8% was for the women who have ever become pregnant, Chi-Square81.724, Sig 0.000, Df 4The researcher point of view is multigravida women is more likely to be infected than nulligravida due to hormonal effects.These results are approximately agreement with (Essa & Hussein, 2018) (23) who found (%56.6) of infected women get pregnancy for 3-5 times.This study illustrates the infected women who have parity between (4-6) is having a higher ratio of 39.3%, then 31.0% for women who have parity between (1-3), parity 7and more is 22.8%, and finally the infected women who have no children get the percent 6.9%, Chi-Square33.290, Sig 0.000, DF3.The researcher point of view is the multipara women more likely to get vaginal infection because of hormonal fluctuation due to breast feeding or due to acquired infection during labor normally or cesarian. These results are disagreement with (Rathod & S., 2016) (23) who found (72.5%) women with vaginitis were nulliparous, (20%) were primipara, (5%) were second para and the remaining (2.5%) were para three and above.The study noted that most infected women 59.3% didn`t have any abortion status, lesser percent 3.4% found in women who have abortion between 4-6 times, chi-Square68.8693.503, Sig 0.000, Df 2.The researcher point of view is the women who exposing to curettage is more likely to acquired vaginal infection.These results are disagreement with (Essa & Hussein, 2018) (23) who found that 13.7% of infected women are having Abortion multiple times.This study reveals that majority of women with vaginal infection were higher percentage in non-pregnant women in 91.0% of them, and the rest percentage 5.5% and 3.4% among pregnant and those who have suspicious pregnancy, Chi-Square 217.338, Sig 0.000, Df 2.The researcher point of view is in pregnancy status estrogen hormone increase and lead to increase occurrence vaginal candidiasis.These results are disagreement with (Saeed et al, 2016) (24) who found the lesser ratio (21.8) of vaginal infected women were nonpregnant, while (78.2) in pregnant women.Our study found that the percentage of vaginal infection women was 94.5% in women non-pregnant, and 3.4% and 2.1% for 2nd trimester and 3rd trimester, Chi-Square 244.028, Sig .000, DF2.The researcher point of view is decreasing immunity in the second and third trimester beside that, in our study approximately 33.8%are of unmarried women also is another causative for increasing the ratio of non-pregnant in our study.Aguin & Sobel, 2015 study results are 90.7 % of patients were in the second and third trimesters, which is in disagreement with our study. Ethical Clearance-formal approval was getting from the Ministry of health /Nineveh health director /Department of Knowledge Management and research/ Management of primary health care center of Hassan Shame and Management of primary health care center of Hassan Shame U2 to collect the data from those primary health care centers.…”
Section: Resultssupporting
confidence: 92%